Could coronavirus 2019-infected disease patients get cope with the treatment?: A qualitative study - Fery AM Mendrofa; Umi Hani; Yuni Nurhidayat (International Journal of Public Health Science (IJPHS), 2021)
A pandemic of a novel coronavirus-infected disease is currently ongoing in the world. Most patients have to be isolated due to the treatments. This study aimed to make sense of how patients with coronavirus-infected disease understand and experience infectious isolation. The research used a qualitative design with a phenomenological approach. Data collection was conducted with in-depth interviews of nine patients with coronavirus disease-2019 (COVID-19) confirmed who had been in the isolation room. The analysis was conducted on interview transcripts by organizing keywords found into categories, sub-themes, and themes based on Colaizzi's approach. The results indicated that the participants experienced fright due to the isolation and attempted to integrate their isolation experiences. Isolation highlighted a sense of threat posed by cross-infection, a threat that participants experienced as originating from others and from themselves to others. Participants described feeling changes experienced after several days of treatment. Participants reported various symptoms of the disease and received careful care while in isolation. They still communicate with family. Isolated patients are able to deal with the treatment by improving their coping strategies. Participants reported the most support from their families, even from a distance. Future research could explore experiences of isolation from family and staff perspectives and identify the psychological aspect in caring for the COVID-19 patients.